PENGHAMBATAN AKTIFASI NFκ κκ κB OLEH CAPE (CAFFEIC ACID PHENETHYL ESTER), KOMPONEN AKTIF MADU LEBAH (HONEYBEE HIVES),PADA HUVEC’S (HUMAN UMBILICAL VEIN ENDOTHELIAL CELLS) YANG DIPAPAR LDL TEROKSIDASI - Rohman, Mohammad Saifur; Rastini, Endah Kusuma; Sarbini, Dwi; A W, Titi; Widodo, Widodo; Sargowo, Djanggan (Fakultas Kedokteran Universitas Brawijaya, 2006)
The high prevalence of cardiovascular morbidity and mortality caused by complication of atherosclerosisneeds an optimal effort to prevent the atherosclerosis progression and complication. Atherogenesis is a chronicinflammatory process which could be prevented via the inhibitionof NF?B, a known key transcription factor involved in inflammatory process. An active component of honeybee hives, CAPE (Caffeic Acid Phenethyl Ester), is believed to inhibit inflammatory process via the inhibition of NF?B activation. However, it remains uncertain whetherCAPE inhibits NF?B activation in endothelial cells. This study therefore was aimed to examine the molecular mechanism of CAPE mediated NF?B inactivation in OxLDL-treated HUVEC?s. Immunohistochemistry using p50 antibody was applied to detectthe migration of NF?B (p50-p65 complex) from inactive form in cytoplasmto active form in nucleus.